Near-field thermodynamics and nanoscale energy harvesting. (7th October 2015) - Latella, Ivan; Pérez-Madrid, Agustín; Lapas, Luciano C; Rubi, J Miguel
Abstract: We study the thermodynamics of near-field thermal radiation between two identical polar media at different temperatures. As an application, we consider an idealized energy harvesting process from sources at near room temperature at the nanoscale. We compute the maximum work flux that can be extracted from the radiation in the near-field regime and compare it with the corresponding maximum work flux in the blackbody regime. This work flux is considerably higher in the near-field regime. For materials that support surface phonon polaritons, explicit expressions for the work flux and an upper bound for the efficiency as functions of the surface wave frequency are obtained.